Assessment of quality of life in outpatients with osteoarthritis (Journal of Medical Science, 2017)
Introduction. Osteoarthritis is a chronic and one of the most often appearing causes of the afflictions on the part of the motor organ. A chronic condition has a negative impact on all areas of human functioning. Its occurrence, but mainly the severity of its symptoms results in significant reduction in quality of life, which is why it is important to assess the effects of the treatment process and rehabilitation. Aim. Assessment of quality of life of patients with osteoarthritis as regards variables such as age, gender, duration of the disease. Material and Methods. The study includes a group of 40 patients diagnosed with osteoarthritis treated in the Health Centre of General Physicians in Mieścisko, Poland in the period from October 2014 to January 2015. The tool which was used to investigate the quality of life of people with osteoarthritis was the Polish version of the scale Arthritis Impact Measurement Scales 2 (AIMS-2). Results. The lowest level of the quality of life was indicated by the subjects in the areas of: arthritis pain (6.54 ± 1.96), walking and bending (6.51 ± 2.81) and mobility (7.21 ± 2.06). The highest level of quality of life occurred in the areas of: support from family and friends (1.56 ± 2.16), household tasks (2.47 ± 3.16), self-care (2.50 ± 2.92), arm function (2.58 ± 2.72), hand and finger function (2.71 ± 3.03), work (2.67 ± 2.38) and mood (3.14 ± 1.56). The youngest participants obtained a result of higher level of the quality of life, which was subject to deteriorate with age. Conclusions. Patients with osteoarthritis require a permanent, comprehensive, multifaceted and multidirectional proceedings in order to improve comfort and quality of life.